ANCIENT CRAFTS AND HOUSEHOLD OCCUPATIONS OF THE INHABITANTS OF JIZZAKH OASIS - Kovulov Jurabek (Journal Park Publishing, 2022)
This article provides detailed information about the types of local crafts and household occupations of the residents of the Jizzakh oasis and these types of crafts were created according to the unique climatic conditions and geographical location of the Jizzakh oasis. There is also talk about professions that serve to meet household needs.
Keywords: weaving; pottery; blacksmithing